Applying Neo-Republican Theory to Welfare to Work Practices: Rules and Arbitrary Power in Mandatory Work Programmes in the Netherlands. Issue 2 (15th April 2023) - Eleveld, Anja
Abstract : Drawing on the neo-republican theory of non-domination and a qualitative case study conducted in three Dutch municipalities, this article explores the extent to which external rules are able to prevent arbitrary power in relationships between welfare officers and work supervisors, on the one hand, and welfare recipients participating in mandatory work programmes, on the other hand. It concludes that external rules were insufficiently implemented in the three municipalities in question. In addition, it found that rules cease to be capable of constraining arbitrary power where institutional contexts themselves are unpredictable and insecure. Under these conditions, welfare recipients may seek to avoid risks and act in accordance with the preferences (or their expectation of the preferences) of the welfare officer or work supervisor by playing the role of the 'good recipient' instead of relying on available rules of a protective nature or rules that enable them to have a say in their participation in mandatory work programmes.